THE STUDENTS’ RESPONSE TO IMPLEMENTATION OF TEACHING READING BY USING JIGSAW TECHNIQUE AT ISLAMIC INSTITUTE - Illananingtyas, Tenika (JURNAL KOULUTUS, 2019)
Abstract The aim of study was to describe the implementation of teaching reading by using jigsaw technique for at Islamic Institute, includingthe lecture‟s preparation in teaching reading by using jigsaw, the steps of teaching reading, the teaching media, the students‟ response and the obstacles faced by the lecturer. This research used descriptive qualitative approach as a research design. The subject was 45 students of the second semester. The methods used in collecting the data were observation, interview, and documentation. The data were collected by using three instruments: observation sheets, an interview guide, and a questionnaire. Based on the data analysis, it was found that the English lecturer at the Islami Institute used Jigsaw Technique as a model.The data analysis was based on three concurrent flows of activities, they were: data reduction, data display, and verification.The result of this study showed that the students like to learn reading in English by using Jigsaw Technique. Keywords: reading, teaching reading, and jigsaw technique